Multiwall carbon nanotube-nematic liquid crystal composite system: preparation and characterization. Issue 5 (25th March 2021) - Yadav, Geeta; Agrahari, Kaushlendra; Manohar, Rajiv
Abstract: The present study reveals the efficacious change in carbon nanotube (CNT) doped nematic liquid crystals (NLC). Herein, the optical and dielectric properties have been measured and a notable change in CNT doped systems is observed in compare to pristine NLC. Modification in different parameters of pristine LC material has shown its strong dependence on the concentration of CNTs. For optical study the photoluminescence, UV-absorbance, and Fourier transform infrared spectroscopy (FTIR) has been performed. An enhancement in photoluminescence without any shift in peak value is observed for both composite systems. In UV-absorbance study, it is noticed that absorbance has been increased after doping the CNTs in NLC system. The constructive combination of emerging waves might be the reason behind such enhancement. FTIR study confirms the influence of CNTs on the molecular dynamics of NLC. Dielectric measurement shows the enhanced value to dielectric permittivity and reduction in dielectric loss at lower frequency region. Conductivity changes its value up to double unit, since the CNTs are highly conducting along the long axis. A shift in relaxation frequency for both composites has been observed in tan delta study. Graphical Abstract: